PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN KAS TERHADAP LIKUIDITAS PADA PT. ULTRAJAYA MILK INDUSTRY DAN TRADING COMPANY, Tbk. - Dewi Lestari; N. Rusnaeni N. Rusnaeni (Universitas Pamulang, 2018)
Abstract The purpose of this research is to know the rotation of receivable at similar company of industry (Milk Management), to know the cash turnover in similar company of industry (Milk Management), and to know how big influence of receivable turnover and cash turn over to liquidity in similar industry Milk Management). The method of research conducted by the author in preparing the thesis is descriptive quantitative, which is doing research that describes the financial condition of the company expressed in the form of numbers. The data used are secondary data in the form of financial statements of Ultrajaya Milk Industry & Trading Company, Tbk. for a period of 10 years from 2005-2014, obtained through ICAMEL (Indonesian Capital Market Electronic Library). The analysis method used is multiple linear regression analysis, classical assumption test, correlation coefficient, determination coefficient and hypothesis test. Based on the results of data analysis, multiple linear regression analysis results obtained regression equation Y = -44.362 0.587X1 0.108X2. Simultaneously variable receivable turnover and cash turnover affect the liquidity it can be seen from the value of f arithmetic ≥ f table (12, 404 ≥ 9.27). Keywords : receivable turnover, cash turnover, and liquidity.